2009
DOI: 10.1088/0967-3334/30/7/004
|View full text |Cite
|
Sign up to set email alerts
|

Measurement errors in multifrequency bioelectrical impedance analyzers with and without impedance electrode mismatch

Abstract: The purpose of this study is to compare measurement errors in two commercially available multi-frequency bioimpedance analyzers, a Xitron 4000B and an ImpediMed SFB7, including electrode impedance mismatch. The comparison was made using resistive electrical models and in ten human volunteers. We used three different electrical models simulating three different body segments: the right-side, leg and thorax. In the electrical models, we tested the effect of the capacitive coupling of the patient to ground and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 16 publications
3
36
0
Order By: Relevance
“…In this study the obtained EBI spectra agree with the EBI spectra reported in [4] and obtained with electrode mismatch. The deviation observed at high frequencies indicates a kind-of inductive behavior present in the measurements obtained with a single electrode.…”
Section: A Skin-electrode Impedance Mismatchsupporting
confidence: 90%
See 3 more Smart Citations
“…In this study the obtained EBI spectra agree with the EBI spectra reported in [4] and obtained with electrode mismatch. The deviation observed at high frequencies indicates a kind-of inductive behavior present in the measurements obtained with a single electrode.…”
Section: A Skin-electrode Impedance Mismatchsupporting
confidence: 90%
“…In EBI measurements the presence of electrode impedance mismatch can affect the impedance estimation as shown in [4]. In this study the obtained EBI spectra agree with the EBI spectra reported in [4] and obtained with electrode mismatch.…”
Section: A Skin-electrode Impedance Mismatchsupporting
confidence: 88%
See 2 more Smart Citations
“…The results show that at low frequencies the frequency response of the output impedance is dominated by effects predicted by the model, while at high frequencies the determining factor is the unavoidable output parasitic capacitance. The validation has been done only with two structures, but any other current source topology will also suffer this effect and most commercial impedance analysers have high errors at high frequencies (Bogonez-Franco et al 2009). The load-in-the-loop structure has the advantage of being very simple and, with modern operational amplifiers, the output impedance frequency response that can be obtained is enough for bioimpedance applications and is limited at high frequencies by a physical cause that is shared with other structures.…”
Section: Frequency Effectsmentioning
confidence: 99%